Benchmarking Australian mental health court liaison services – results from the first national study. Issue 5 (3rd September 2019) - Davidson, Fiona; Heffernan, Ed; Hamilton, Bruce; Greenberg, David; Butler, Tony; Burgess, Philip
ABSTRACT: Mental health court liaison services (CLS) are a key component of the forensic mental health sector in Australia with a service present in each state and territory to identify and treat those with mental illness in contact with the courts. To date, limited research has been undertaken into how these services are delivered and which model is most effective. This paper describes the process and outcomes of the first national collaboration to trial a set of key performance indicators (KPIs) for Australian mental health court liaison services (CLS) using a benchmarking model. A set of nationally endorsed KPIs were found to be useful and relevant to policy and practice in terms of enabling services to compare resources and highlight areas for quality improvement. Wide variation in performance across services was observed. The ability of smaller services to provide data emerged as an issue, with several identifying the need to improve reporting capability. Benchmarking of specialised forensic mental health services was found to be a valuable process for services. Future collaborations for CLS may include refinements to the KPIs and will continue to enhance the knowledge base of this specialised area of forensic mental health service provision.